Tingkat Pengetahuan Siswa Tentang Permainan Bulutangkis Kelas VIII di SMP Negeri 1 Telukjambe Barat Kabupaten Karawang - Raafi Fadilla Majid; Rekha Ratri Julianti; Rahmat Iqbal (Peneliti.net, 2021)
This study aims to determine the level of knowledge of students about the game of badminton in class VIII at SMP Negeri 1 Telukjambe Barat, Karawang Regency. The research method uses a survey method with a questionnaire/questionnaire. Based on the results of the study, it can be concluded that the level of knowledge of students about the game of badminton in class VIII at SMP Negeri 1 Telukjambe Barat, Karawang Regency for the level of knowledge of students about the game of badminton is in the